2023
DOI: 10.1039/d3fo00683b
|View full text |Cite
|
Sign up to set email alerts
|

Selenium deficiency caused hepatitis in chickens via the miR-138-5p/SelM/ROS/Ca2+ overload pathway induced by hepatocyte necroptosis

Xinyue Sun,
Wenyue Zhang,
Xu Shi
et al.

Abstract: Selenium deficiency cause oxidative stress through upregulation of miR-138-5p targeting SelM, which disrupted Ca2+ and energy metabolic homeostasis allowing hepatocyte necroptosis leading to hepatitis in chickens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Se deficiency destroys the body's REDOX homeostasis, and ROS accumulation promotes the occurrence of oxidative stress in mastitis [37]. Previous studies have confirmed that Se deficiency causes inflammatory damage through oxidative stress in chickens [38], mice [39], carps [40], and cattle [41]. The present study established the Se-deficient MAC-T cell model in vitro by continuous delivery culture using FBS with very low Se concentrations.…”
Section: Discussionmentioning
confidence: 59%
“…Se deficiency destroys the body's REDOX homeostasis, and ROS accumulation promotes the occurrence of oxidative stress in mastitis [37]. Previous studies have confirmed that Se deficiency causes inflammatory damage through oxidative stress in chickens [38], mice [39], carps [40], and cattle [41]. The present study established the Se-deficient MAC-T cell model in vitro by continuous delivery culture using FBS with very low Se concentrations.…”
Section: Discussionmentioning
confidence: 59%